Modeling the air-soil exchange, secondary emissions and residues in soil of polychlorinated biphenyls in China - Song Cui (Nature Portfolio, 2017)
Abstract The present study investigated the environmental distribution and fate of low molecular weight (LMW) polychlorinated biphenyls (PCBs) in China using the ChnGIPERM (Chinese Gridded Industrial Pollutants Emission and Residue Model), in which the air-soil exchange, spatial-temporal variations and the heterogeneity of secondary emission and residue in the non-source areas were studied. The model simulated the temporal and spatial variations of the PCB28 concentration in soils and air which agreed well with historical monitoring data across China. The long-range atmospheric transport (LRAT) and temperature was identified as the major factor affecting the distribution patterns of the secondary emissions and residues. Soil residue was considered as important environmental fate of PCB28. However, the intensity of an emissions source and the distance with non-source area strongly affected the spatial and temporal variations of PCB28 residues in soil. Several factors strongly impacted the distribution characteristics and air-soil exchange of PCB28, including emission patterns, atmospheric transport, soil organic carbon (SOC), soil vertical transfer, ambient temperature, and precipitation.